Assessment of the anti-crisis potential of industrial enterprises - T. V. Kakatunova; M. V. Maksimkin (Путеводитель предпринимателя)
The classification of industrial enterprises at different stages of pre-bankruptcy and bankruptcy is developed. Indicators for assessing the material, technical and innovative potential of enterprises located at different stages of pre-bankruptcy and bankruptcy, as well as measures aimed at their modernization, are proposed.